Does sex influence the diagnostic evaluation of autism spectrum disorder in adults?. (October 2016) - Wilson, C Ellie; Murphy, Clodagh M; McAlonan, Grainne; Robertson, Dene M; Spain, Debbie; Hayward, Hannah; Woodhouse, Emma; Deeley, P Quinton; Gillan, Nicola; Ohlsen, J Chris; Zinkstok, Janneke; Stoencheva, Vladimira; et al.
It is unknown whether sex influences the diagnostic evaluation of autism spectrum disorder, or whether male and female adults within the spectrum have different symptom profiles. This study reports sex differences in clinical outcomes for 1244 adults (935 males and 309 females) referred for autism spectrum disorder assessment. Significantly, more males (72%) than females (66%) were diagnosed with an autism spectrum disorder of any subtype (x 2  = 4.09; p  = 0.04). In high-functioning autism spectrum disorder adults (IQ > 70; N = 827), there were no significant sex differences in severity of socio-communicative domain symptoms. Males had significantly more repetitive behaviours/restricted interests than females ( p  = 0.001, d = 0.3). A multivariate analysis of variance indicated a significant interaction between autism spectrum disorder subtype (full-autism spectrum disorder/partial-autism spectrum disorder) and sex: in full-autism spectrum disorder, males had more severe socio-communicative symptoms than females; for partial-autism spectrum disorder, the reverse was true. There were no sex differences in prevalence of co-morbid psychopathologies. Sex influenced diagnostic evaluation in a clinical sample of adults with suspected autism spectrum disorder. The sexes may present with different manifestations of the autism spectrum disorder phenotype and differences vary by diagnostic subtype. Understanding and awareness of adult female repetitive behaviours/restricted interests warrant attention and sex-specific diagnostic assessment tools may need to be considered.